2009
DOI: 10.1002/biot.200800291
|View full text |Cite
|
Sign up to set email alerts
|

Substrate and water adsorption phenomena in a gas/solid enzymatic reactor

Abstract: The adsorption of water and substrates to dry deposited alcohol dehydrogenase from Lactobacillus brevis (LBADH) is studied in a continuous enzymatic gas/solid reactor. This work is aiming at obtaining a deeper and more thorough understanding of the enzyme microenvironment in the gas/solid system of acetophenone reduction with concomitant oxidation of 2-propanol. Extensive water adsorption studies showed that the effect of sucrose in the enzyme preparation on the water adsorption isotherm is significant for wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…This decrease shows that salt (from suspension buffer before enzyme drying) as well as glycosylation strongly influence the water adsorption, as already observed with other proteins. [47] The shape of experimental water sorption and desorption curves were very similar to water sorption curves previously obtained for other proteins and followed the pattern of the BET model. [47][48][49] Moreover, the value of 0.063 mg of water per mg of dry protein found for BET monolayer water was in the range 0.05-0.07 found for other proteins.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…This decrease shows that salt (from suspension buffer before enzyme drying) as well as glycosylation strongly influence the water adsorption, as already observed with other proteins. [47] The shape of experimental water sorption and desorption curves were very similar to water sorption curves previously obtained for other proteins and followed the pattern of the BET model. [47][48][49] Moreover, the value of 0.063 mg of water per mg of dry protein found for BET monolayer water was in the range 0.05-0.07 found for other proteins.…”
Section: Discussionsupporting
confidence: 80%
“…[47] The shape of experimental water sorption and desorption curves were very similar to water sorption curves previously obtained for other proteins and followed the pattern of the BET model. [47][48][49] Moreover, the value of 0.063 mg of water per mg of dry protein found for BET monolayer water was in the range 0.05-0.07 found for other proteins. [48,49] The absence of hysteresis between adsorption and desorption indicated that there was no irreversibly bound water on the protein.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…It allows in particular revealing the formation of a water monolayer and its weight, and the occurrence of free water for higher a w [17]. Yet, BET model is considered as a good mathematical tool to characterize the water adsorption isotherm and to determine the size of the monolayer for proteins, and this for a w up to 0.4.…”
Section: Water Adsorption By Immobilized Calb Studied By Water Adsormentioning
confidence: 99%
“…There have been very few experimental studies addressing both water and substrates adsorption on enzymes [17,18], although these adsorption phenomena might be a way to better elucidate enzyme kinetics and specificity. Recently we have studied molecular mechanism of hydration of free, deglycosylated, and desalted pure CALB in the gas phase.…”
Section: Introductionmentioning
confidence: 99%